Tunable Electronic Structure in Twisted Bilayer WTe2 - Chen, Zi-Si; Huang, Lu; Guo, Wen-Ti; Zhong, Kehua; Zhang, Jian-Min; Huang, Zhigao (Frontiers in Physics, 2022)
The Moiré pattern restricts the electronic states of transition metal bilayers, thus extending the concept of the magic angle found in twisted bilayer graphene to semiconductors. Here, we have studied the electronic structure of the twisted bilayer WTe2 using first-principles calculations. Our result shows that twist significantly changes the band structure resulting in the bandgap engineering when the twisted bilayer of WTe2 is turning to a specific angle. The electronic structure is changed by the change of the twist angle. Interestingly, a semiconductor-to-metal phase transition is found at a twist angle of 15 degree. Our results provide a reference for the regulation of two-dimensional band structures. These results are important for understanding the electronic structure of twisted systems and for future applications in electronic devices.